Receding horizon H∞ guaranteed cost tracking control for microwave heating medium with temperature-dependent permittivity. (February 2018) - Zhong, Jiaqi; Liang, Shan; Xiong, Qingyu
Abstract: This paper considers the temperature spectrum tracking control of microwave heating model, in the presence of asymmetrical input saturation, nonhomogeneous Neumann boundary condition and temperature-dependent permittivity. The sufficient condition for the existence of receding horizon H ∞ guaranteed cost control is proposed based on the derived finite-dimensional ordinary differential equation (ODE) error model. Furthermore, by on-line updating and solving linear matrix inequalities (LMIs) optimization problem, the constrained tracking controller can be obtained in the sense of minimizing H ∞ norm and satisfying the quadratic cost performance. The proposed control strategy is implemented on a one-dimensional cavity heating model and its performance is evaluated through the simulation. Highlights: A receding horizon H ∞ guaranteed cost control is proposed to regulate temperature spectrum for the microwave heating process with asymmetrical input saturation. A sufficient LMIs condition is derived to satisfy both of the H ∞ norm and quadratic cost performance. The control strategy is implemented on the one-dimensional cavity heating model with temperature-dependent permittivity.